Pro-Family Discourse: A Medium for the Perpetuation of Hegemonic Masculinity by AILA - Satiti, Nur Latifah Umi; Triastuti, Endah (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
This research focuses on the debate on gender justice discourse in Indonesia, particularly its origins during the Draft Law on Criminal Acts of Sexual Violence (RUU-TPKS). Simultaneously, anti-sexual violence discourse began to emerge from women's groups. However, on the other hand, the draft ignite rejection from other group named AILA (Aliansi Cinta Keluarga). AILA narrates their discourse as a form of protection for families. Hence, this paper investigates the discourse distributed by AILA through online media, such as websites, and social media. this research will refer to Foucault's argument that underscores that discourse is a narrative vessel that is never neutral and never value-free, because discourse is a tool in producing knowledge that is easily accepted and translated into behavior. According to Foucault, the embodiment of discourse into behavioral forms occurs through institutions that serve power. In other words, in the discourse ecosystem, there are institutions that guarantee discourse. By using qualitative method, data were collected through documentation and observation. The findings show that AILA's discourse on family and women as mothers has become a cover for marginalizing women. By framing the pro-family narrative, AILA distributes misconceptions about feminism by portraying feminists as a group of women who hate men, destroy families, and promote prostitution and promiscuity. Through AILA's posts on their social media accounts, researchers can observe how they utilize the power of various actors in producing discourse. Instead of using family discourse to gender justice in Indonesia, the researchers conclude that AILA actually distances women from gender justice agendas, thus preventing them from accessing policies relevant to their lives.